Profil kemampuan koneksi matematis mahasiswa pendidikan matematika pada awal perkuliahan trigonometri - Andriani, Suci; Armis, Armis (Jurnal Pendidik Indonesia, 2025)
This study aims to describe the mathematical connection ability of first-semester students at the beginning of the trigonometry course. The research subjects were first-semester students of the Mathematics Education Study Program in the 2024/2025 academic year. The research method used was descriptive with a mixed-method approach, combining both quantitative and qualitative data. The research procedure consisted of three stages: (1) development of research instruments, (2) administration of a mathematical connection ability test, and (3) analysis of student responses. The instrument used was a trigonometry test that included indicators of mathematical connection ability. The results show that at the beginning of the course, students' mathematical connection abilities were still relatively low. The percentage of students in the very good category was only 0.83%, good category 10%, fair category 40.83%, poor category 45.84%, and very poor category 2.5%. Further analysis revealed that students in the high category were able to connect mathematical concepts and apply them to real-world problems but struggled to relate different mathematical representations. Meanwhile, students in the low category had difficulties in all aspects of mathematical connections, including linking concepts, connecting representations, and applying mathematics to real-life situations.